Study the Quality of Nasopharyngeal plans Using Evaluation Indexes of IMRT and VMAT Treatment planning Techniques (Baghdad Science Journal, 2024)
Radiation treatment has long been the conventional approach for treating nasopharyngeal cancer (NPC) tumors due to its anatomic features, biological characteristics, and radiosensitivity. The most common treatment for nasopharyngeal carcinoma is radiotherapy. This study aimed to assess the better quality of radiotherapy treatment techniques using intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT). The VMAT and IMRT are comparative techniques. Forty patients with nasopharyngeal carcinoma and forwarded for radiotherapy were treated with both advanced techniques, IMRT and VMAT, using eclipse software from Varian. The x-ray energy was set at 6 MV. The total prescribed dose was 70 Gy. The results show that the VMAT had better tumor coverage than the IMRT. Regarding quality indices, the IMRT shows a better dose homogeneity, while the VMAT gives better gradient and conformity indices. The best technique that reduces the dose to the right eye, optic chiasm, and thyroid is VMAT, while the esophagus and spinal cord are protected better with IMRT. The VMAT shows a special effect for IMRT for treating nasopharyngeal carcinoma.